Use of a Gigli Saw as a Substitute Osteotomy Tool When Oscillating Saw Malfunctions Occur During Hip Arthroplasty. Issue 12 (21st October 2022) - Kong, Keyu; Chang, Yongyun; Yu, Degang; Mao, Yuanqing; Zeng, Yiming; Yan, Mengning; Zhai, Zanjing; Li, Huiwu
Abstract : Objective: The oscillating saw has some inherent disadvantages, such as notch formation and blood splash. The objective is to introduce the Gigli saw as a substitute osteotomy tool when oscillating saw malfunctions occur during surgery. Methods: During our retrospective study, 120 patients (120 hips) who underwent primary total hip arthroplasty (THA) because of femoral neck fracture, femoral head necrosis, developmental hip dysplasia (Crowe I), or primary osteoarthritis between October 2017 and April 2020 at our institute were included. Sixty patients (26 men and 34 women) with a mean age of 67.3 years (±15.1 years) underwent femoral neck osteotomy using a Gigli saw. The other 60 patients (32 men and 28 women) with a mean age of 64.4 years (±18.8 years) underwent femoral neck osteotomy using an oscillating saw. Intraoperative evaluations, including osteotomy time, osteotomy height, number of notch formations, and blood splash generation, were performed. Routine anteroposterior views of the pelvis and proximal femur were obtained for all patients after surgery. Results: The mean osteotomy times were 26.60 ± 14.80 s and 31.80 ± 14.20 s with the oscillating saw and Gigli saw, respectively ( t  = 1.964, P  = 0.0519). The mean osteotomy heights were 1.26 ± 0.22 cm and 1.20 ± 0.14 cm with the oscillating saw and Gigli saw, respectively ( t  = 1.782, P  = 0.0773). The use of a Gigli saw did not result in bone notch formation or blood splash generation when multiple blood splashes were generated in the oscillating saw group. Postoperative radiographs showed no prostheses malposition in the Gigli saw and oscillating saw groups. Conclusion: The Gigli saw has various advantages and can be a substitute tool for femoral neck osteotomy during THA when oscillating saw malfunctions occur. Abstract : Oscillating saw malfunction occurs frequently when implementing femoral neck osteotomy. This study aimed to introduce the Gigli saw as a novel substitute osteotomy tool with various advantages such as less notch formation and less blood splash generation.